Bağlanma stilleri ve duygusal yeme ilişkisinde duygusal tepkisellik ve bilişsel duygu düzenleme stratejilerinin aracı rolü - Akoğlu Günbatan, Melda (İstanbul Medipol Üniversitesi, Sosyal Bilimler Enstitüsü, 2022)
Mevcut araştırmada, bağlanma stilleri ve duygusal yeme ilişkisinde, duygusal tepkisellik ve bilişsel duygu düzenleme stratejilerinin aracılık etkisi incelenmiştir. Araştırmaya katılan 437 katılımcı, 18-33 yaş aralığındadır. Katılımcılara öncelikle Sosyodemografik Bilgi formu, ardından Yakın İlişkilerde Yaşantılar Envanteri (YİYE-II), Hollanda Yeme Davranışı Anketi (DEBQ), Duygusal Tepkisellik Ölçeği (DTÖ) ve Bilişsel Duygu Düzenleme Ölçeği (BDDÖ) uygulanmıştır. Çalışmada uygulanan korelasyon analizlerine göre, bağlanma alt boyutları ile duygusal tepkisellik, bilişsel duygu düzenleme ve duygusal yeme arasında; duygusal tepkisellik ile bilişsel duygu düzenleme ve duygusal yeme arasında ve bilişsel duygu düzenleme ile duygusal yeme arasında anlamlı ilişkiler bulunmuştur. Aracılık analizi için, bootstrap yöntemlerinden olan çoklu model analizini araştırmak amacı ile SPSS PROCESS (Model 6) makrosundan faydalanılmıştır. Analiz sonucuna göre, kaygı boyutu ile duygusal yeme ilişkisinde duygusal tepkisellik ve adaptif olmayan bilişsel duygu düzenlemenin aracı rolü olduğu bulgusu çıkmıştır. Literatür kapsamında elde edilen bulgular tartışılması ile birlikte çalışmanın sonunda öneriler ve kısıtlara yer verilmiştir.

In the recent study, the mediating effect of emotional reactivity and cognitive emotion regulation strategies in the relationship between attachment styles and emotional eating was examined. 437 participants participating in the study are between the ages of 18-33. Sociodemographic information questionnaire, Experiences in close relationships-Revised (ECR-R), Dutch Eating Behavior Questionnaire (DEBQ), Emotion Reactivity Scale (ERS) and Cognitive Emotion regulation Questionnaire (CERQ) were applied to the participants, respectively. According to the correlation analysis applied in the study, significant positive correlations were found between attachment sub-dimensions and emotional reactivity, cognitive emotion regulation, emotional eating; between emotional reactivity and cognitive emotion regulation, emotional eating; between cognitive emotion regulation and emotional eating. For mediation analysis, SPSS PROCESS (Model 6) macro was used to investigate multi-pattern analysis, which is one of the bootstrap methods. As a result of analysis, it was found that emotional reactivity and non-adaptive cognitive emotion regulation had a mediating role in the relationship between the anxiety dimension and emotional eating. Findings obtained within the scope of the literature with discussion are included in the recommendations and constraints section at the end of the study.
The mediator role of emotional reactivity and cognitive emotion regulation strategies in the relationship of attachment styles and emotional eating
Keywords: Bağlanma Stilleri; Duygusal Yeme; Duygusal Tepkisellik; Bilişsel Duygu Düzenleme; Attachment Styles; Emotional Eating; Emotional Reactivity; Cognitive Emotion Regulation